Deterritorialized Border, Differential Inclusion and the Nation-state: Brazilian World War II Refugee Selection Commission - Ruseishvili, Svetlana (2020)
This article discusses the case of the Brazilian World War II Refugee Selection Commission in Europe through the perspective of critical mobility studies. Some preparatory studies and reports of the Commission members, mainly the ones written by Artur Hehl Neiva, its chief in 1946-1947, were investigated. It is argued that the Commission represented a singular form of the Brazilian “whitening” policy in the post-war period. The case is considered as a smart border avant la lettre, that operated through hierarchical classification and differential inclusion of refugees.